Transcriptional programming of immunoregulatory responses in human Langerhans cells - Davies, James; Sirvent, Sofia; Vallejo, Andres F.; Clayton, Kalum; Douilhet, Gemma; Keeler, Patrick S.; West, Jonathan; Ardern-Jones, Michael; MacArthur, Ben D.; Singh, Harinder; Polak, Marta E. (Frontiers in Immunology, 2022)
Human epidermal Langerhans cells (LCs) maintain immune homeostasis in the skin. To examine transcriptional programming of human primary LCs during homeostasis, we performed scRNA-seq analysis of LCs before and after migration from the epidermis, coupled with functional assessment of their regulatory T cell priming capabilities. The analysis revealed that steady-state LCs exist in a continuum of maturation states and upregulate antigen presentation genes along with an immunoregulatory module including the genes IDO1, LGALS1, LAMTOR1, IL4I, upon their migration. The migration-induced transition in genomic state is accompanied by the ability of LCs to more efficiently prime regulatory T cell responses in co-culture assays. Computational analyses of the scRNAseq datasets using SCENIC and Partial Information Decomposition in Context identified a set of migration-induced transcription factors including IRF4, KLF6 and RelB as key nodes within a immunoregulatory gene regulatory network. These findings support a model in which efficient priming of immunoregulatory responses by LCs is dependent on coordinated upregulation of a migration-coupled maturation program with an immunoregulation-promoting genomic module.